Effects of Fire Diurnal Variation and Plume Rise on U.S. Air Quality During FIREX‐AQ and WE‐CAN Based on the Multi‐Scale Infrastructure for Chemistry and Aerosols (MUSICAv0). Issue 16 (20th August 2022) - Tang, Wenfu; Emmons, Louisa K.; Buchholz, Rebecca R.; Wiedinmyer, Christine; Schwantes, Rebecca H.; He, Cenlin; Kumar, Rajesh; Pfister, Gabriele G.; Worden, Helen M.; Hornbrook, Rebecca S.; Apel, Eric C.; Tilmes, Simone; et al.
Abstract: We analyze the effects of the diurnal cycle of fire emissions (DCFE) and plume rise on U.S. air quality using the MUSICAv0 (Multi‐Scale Infrastructure for Chemistry and Aerosols Version 0) model during the FIREX‐AQ (Fire Influence on Regional to Global Environments and Air Quality) and WE‐CAN (Western wildfire Experiment for Cloud chemistry, Aerosol absorption and Nitrogen) field campaigns. To include DCFE in the model, we employ two approaches: a DCFE climatology and DCFE derived from a satellite fire radiative power product. We also implemented two sets of plume‐rise climatologies, and two plume‐rise parameterizations. We evaluate the model performance with airborne measurements, U.S. EPA Air Quality System surface measurements, and satellite products. Overall, including plume rise improves model agreement with observations such as aircraft observations of CO and NOx for FIREX‐AQ and WE‐CAN. Applying DCFE also improves model performance, such as for surface PM2.5 in fire‐impacted regions. The impact of plume rise is larger than the impact of DCFE. Plume rise can greatly enhance modeled long‐range transport of fire‐emitted pollutants. The simulations with plume‐rise parameterizations generally perform better than the simulations with plume‐rise climatologies during FIREX‐AQ, but not for WE‐CAN. The 2019 Williams Flats Fire case study demonstrates that DCFE and plume rise change fire impacts because fire emissions are subject to different meteorology and chemistry when emitted at different times of a day and altitudes. Moreover, DCFE and plume rise also impact local‐to‐regional meteorology and chemical reaction rates. DCFE and plume rise will be included in future MUSICA versions. Plain Language Summary: Fires have significant impacts on U.S. air quality. The characteristics of fires such as diurnal variation and plume rise can largely alter these impacts. We study the impact of fire diurnal variation and plume rise on U.S. air quality using a newly developed modeling system—Multi‐Scale Infrastructure for Chemistry and Aerosols Version 0 (MUSICAv0). Specifically, we employ two approaches to include the diurnal cycle of fire emissions (DCFE) and four approaches to include fire plume rise in the model. The model experiments were conducted for two campaign periods, FIREX‐AQ (Fire Influence on Regional to Global Environments and Air Quality) and WE‐CAN (Western wildfire Experiment for Cloud chemistry, Aerosol absorption and Nitrogen). We compare the model results with airborne measurements, surface measurements, and satellite products over the continental U.S. during the two campaign periods. Overall, including plume rise and/or DCFE improves model agreement with observations of the studied air‐quality‐related chemical species, and the impact of fire plume rise is larger than the impact of the DCFE. A case study also demonstrates that fire plume rise and the DCFE also impact local‐to‐regional meteorology and chemical reaction rates. Key Points: Including plume rise and diurnal cycle of fire emissions (DCFE) overall improves MUSICAv0 model agreement with observations Simulations with plume rise parameterizations generally perform better than the simulations with plume rise climatologies during FIREX‐AQ Plume rise and DCFE impact local‐to‐regional meteorology and chemical reaction rates